2016
DOI: 10.1186/s13690-016-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of children 0–59 months in selected intervention communities in northern Ghana from the africa RISING project in 2012

Abstract: BackgroundPoor nutritional status during childhood and its long-term impact on economic growth and wellbeing is well known. This study assessed the nutritional status of children in selected communities in northern Ghana, to serve as baseline data for the Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) project that sought to improve farm-household nutrition through agriculture.MethodsA cross-sectional study was conducted among children 0–59 months in selected communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 31 publications
(32 reference statements)
4
37
3
Order By: Relevance
“…This implies that, though stunting and underweight are decreasing in the region, household food security does not seem to improve, as reflected in the higher prevalence of wasting found in present study. The lower prevalence of stunting and underweight recorded in this study compared to those reported in the 2014 demographic and health survey has also been documented by recent studies in the Northern region [9,22]. A higher proportion of children in the study sample consumed a diversified diet from at least four food groups.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…This implies that, though stunting and underweight are decreasing in the region, household food security does not seem to improve, as reflected in the higher prevalence of wasting found in present study. The lower prevalence of stunting and underweight recorded in this study compared to those reported in the 2014 demographic and health survey has also been documented by recent studies in the Northern region [9,22]. A higher proportion of children in the study sample consumed a diversified diet from at least four food groups.…”
Section: Discussionmentioning
confidence: 41%
“…As Ghana strives to attain the Sustainable Development Goals (SDGs) by the year 2030, ensuring nutritional well-being is key [8]. Government and non-governmental organizations in response to the high prevalence of stunting among children in the Northern region have initiated some interventions to decrease it [9]. For these interventions to have the most impact on stunting, data on the predictors and the strong determinants of stunting affecting these children is critical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 On a global scale, malnutrition is associated with one third of the deaths in children under the age of 5. 1 The paradoxical phenomenon of the coexistence in the same family of chronically undernourished children and their overweight/obese mothers has been observed in several studies, suggesting an emerging problem in developing countries. 5 Nutritional status has several implications for the health and the welfare of populations, particularly in periods of rapid growth and development, such as pregnancy and early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In São Tomé and Príncipe (STP), an economically disadvantaged African country, 1 in 15 children dies before the age of 5, and malnutrition may account for more than 50% of these deaths. 3,4 On a global scale, malnutrition is associated with one third of the deaths in children under the age of 5.…”
Section: Introductionmentioning
confidence: 99%